2020
DOI: 10.1186/s13063-020-4183-9
|View full text |Cite
|
Sign up to set email alerts
|

Outcome reporting in neonates experiencing withdrawal following opioid exposure in pregnancy: a systematic review

Abstract: Background: Neonatal withdrawal secondary to in utero opioid exposure is a growing global concern stressing the psychosocial well-being of affected families and scarce hospital resources. In the ongoing search for the most effective treatment, randomized controlled trials are indispensable. Consistent outcome selection and measurement across randomized controlled trials enables synthesis of results, fostering the translation of research into practice. Currently, there is no core outcome set to standardize outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…duration of IWS, relapse, post-ICU physical dependence and healthrelated quality of life). Developing a core outcome set for studies examining IWS, as for conditions such as neonatal abstinence syndrome or delirium [45,46], may address the latter issues. Shared definitions of important and meaningful outcomes would allow combination and comparison of study outcomes and assist in the development of robust conclusions about effectiveness of interventions.…”
Section: Discussionmentioning
confidence: 99%
“…duration of IWS, relapse, post-ICU physical dependence and healthrelated quality of life). Developing a core outcome set for studies examining IWS, as for conditions such as neonatal abstinence syndrome or delirium [45,46], may address the latter issues. Shared definitions of important and meaningful outcomes would allow combination and comparison of study outcomes and assist in the development of robust conclusions about effectiveness of interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis also concluded that morphine was the least effective treatment used to treat NOWS, whereas methadone, buprenorphine, and clonidine were the most effective. Finally, a systematic review by Shan et al 114 evaluated the consistency in reported outcomes of clinical studies conducted in neonates treated for NOWS among 47 publications published between 2007 and 2017 with 107 primary outcomes and 127 secondary outcomes. The authors concluded that outcomes were similar among studies; however, the definitions of the outcomes varied.…”
Section: Clinical Studies Of Opioids In the Treatment Of Nowsmentioning
confidence: 99%
“…LOS and DOT are the conventional primary outcomes used to assess the effectiveness of each medication used during NOWS pharmacotherapy. Several studies have compared the pharmacotherapy with morphine, methadone, and buprenorphine in the treatment of NOWS 112–114 . Table 2 includes recent studies (published since 2015), which included assessment tools, compared treatment options (ie, morphine vs methadone, methadone vs buprenorphine, buprenorphine vs morphine), sample size, study type, DOT, LOS, and the number of patients administered adjunctive therapy.…”
Section: Clinical Studies Of Opioids In the Treatment Of Nowsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Authors of a recent review highlighted that a limited number of studies included families in study design, primarily outcome selection. 13 In neonatology, clinical trial populations are small, and studies are often underpowered to answer additional effectiveness questions or conduct meaningful subgroup analysis. 14,15 This compounds the need and relevance for meta-analysis (or data pooling) of multiple studies' results to answer important questions on interventions' safety and effectiveness.…”
Section: What's Known On This Subjectmentioning
confidence: 99%